Prevalence of changes in oral mucosa in adults in the population of Uberaba, Minas Gerais, Brazil - Paulo Roberto Henrique; Murilo Bazaga Júnior; Vera Cavalcanti de Araújo; José Luís Cintra Junqueira; Cristiane Furuse (Faculdade São Leopoldo Mandic, 2009)
Objective: The aim of this study was to determine the prevalence of oral mucosal alterations among Brazilian adults of the Uberaba, city of Minas Gerais state of Brazil. Methods: A random sample of age, gender, and race was obtained comprising 1 006 individuals over the age of twenty years. Individuals were interviewed and examined according to the Marcucci guide1. Results: Prevalence of oral mucosal alterations in the sample was 54.4%, with 32.2% presenting oral mucosal lesions and 35.2% with normal alterations (12.6% of the individuals exhibited the two conditions). The most common lesion was gingivitis (6.6%) followed by candidiasis (4.5%), fibroma (3.2%), inflammatory fibrous hyperplasia (3.1%), actinic cheilitis (2.4%), traumatic ulcers (1.7%) mucocele (1.2%), minor aphta (1.2%), oral leukoplakia (1.2%). Sublingual varix was the most frequent (9.9%) among the normality conditions, followed by Fordyce spot (6.6%), fissured tongue (3.2%), leukoedema (3.1%), geographic tongue (2.7%), torus mandibularis (2.1%), linea alba (2.1%), hairy tongue (1.4%), torus palatinus (1.0%). Biopsies were performed in 31 clinically indicated cases and no case of oral cancer was observed. Conclusion: Conditions observed among this Brazilian population were essentially the same as those that have been described in other populations around the world. Different factors increased the probability of specific oral mucosal conditions.